2008
DOI: 10.1103/physrevlett.100.217401
|View full text |Cite
|
Sign up to set email alerts
|

Photon Antibunching in the Photoluminescence Spectra of a Single Carbon Nanotube

Abstract: We report the first observation of photon antibunching in the photoluminescence from single carbon nanotubes. The emergence of a fast luminescence decay component under strong optical excitation indicates that Auger processes are partially responsible for inhibiting two-photon generation. Additionally, the presence of exciton localization at low temperatures ensures that nanotubes emit photons predominantly one by one. The fact that multiphoton emission probability can be smaller than 5% suggests that carbon n… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
290
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 254 publications
(301 citation statements)
references
References 39 publications
11
290
0
Order By: Relevance
“…Recent studies of fluorescence antibunching have confirmed that SWNTs are single-photon emitters at low temperatures. 80 For example, the probability that an SWNT will simultaneously emit more than one photon is only 3% up to 10 K, and increases only to 15% at 25 K. Antibunching behavior is more pronounced at low temperatures due to strong localization of excitons, which diminishes the strength of nonlinear interactions between different sites along the nanotube sidewall. 80 Although SWNT antibunching has not yet been observed at room temperature, if single photon emission could be demonstrated under these conditions, nanotubes would be leading candidates for development as quantum optical components.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Recent studies of fluorescence antibunching have confirmed that SWNTs are single-photon emitters at low temperatures. 80 For example, the probability that an SWNT will simultaneously emit more than one photon is only 3% up to 10 K, and increases only to 15% at 25 K. Antibunching behavior is more pronounced at low temperatures due to strong localization of excitons, which diminishes the strength of nonlinear interactions between different sites along the nanotube sidewall. 80 Although SWNT antibunching has not yet been observed at room temperature, if single photon emission could be demonstrated under these conditions, nanotubes would be leading candidates for development as quantum optical components.…”
Section: Discussionmentioning
confidence: 99%
“…80 Specifically, quantum cryptography requires a source of single photons, as sources that emit two or more photons provide opportunities for a compromised transmission. 81 SWNTs could be an exceptional source of single photons because they do not show fluorescence intermittency at room temperature, nor do they photobleach.…”
Section: Optical Properties and Applicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Our results can have important implications in SWNT-based photonics and quantum optics in the light of recent observations of exciton localization in SWNTs due to the presence of disorder. 99 …”
Section: Discussionmentioning
confidence: 99%
“…2 Various schemes for single-photon generation 3 have been proposed, including two-photon down conversion using nonlinear crystals, 4 photon blockade 5 and fluorescence of single molecules, 6 trapped ions and atoms, 7 carbon nanotubes, 8 as well as diamond color centers. 9 Due to their versatility, scalability, and ease to handle, single semiconductor quantum dots (QDs) are amongst the most promising candidates of stable, solid-state emitters for such applications.…”
Section: Introductionmentioning
confidence: 99%